The trouble with Tink - Thorpe, Kiki; Clarke, Judith (New York : Random House Children's Books, 2006)
Tinker Bell, a pots-and-pans fairy who loves fixing things, has lost her hammer and now everything she tries to repair goes wrong, but in order to get her talent back, she may have to visit a former friend who once hurt her feelings
"A Stepping Stone book."
Keywords: Fairies -- Fiction; Repairing -- Fiction; Lost and found possessions -- Fiction; Friendship -- Fiction; Characters in literature -- Fiction